Perillaldehyde improves cognitive function in vivo and in vitro by inhibiting neuronal damage via blocking TRPM2/NMDAR pathway - Yue Qiu; Xian-jun Xue; Geng Liu; Miao-miao Shen; Chun-yan Chao; Jie Zhang; Ya-qi Guo; Qian-qian Niu; Ya-nan Yu; Yu-ting Song; Huan-huan Wang; Shuang-xi Wang; et al. (BMC, 2021)
Abstract Background Vascular cognitive dysfunction in patients with vascular dementia (VD) is a kind of severe cognitive dysfunction syndrome caused by cerebrovascular diseases. At present, effective drugs to improve the cognitive function of VD patients still need to be explored. Transient Receptor Potential Melastatin 2 (TRPM2) channel is a nonspecific cation channel that plays a key role in the toxic death of neurons. Perillaldehyde (PAE) has the protective effect of epilepsy and insomnia and other central nervous system diseases. The aim of this study is to explore whether PAE improves cognitive function in VD rats and to investigate the potential mechanisms in vivo and vitro. Methods VD rats were induced by bilateral common carotid arteries occlusion (2-vessel occlusion [2VO]) and treated with PAE for 4 weeks. The neuroprotective effects of PAE was subsequently assessed by the Morris water maze, hematoxylin-eosin (HE) staining, Golgi staining, electron microscopy, Neuron-specific nuclear protein (Neu N) staining, and TdT-mediated dUTP nick end labeling (TUNEL) staining. After primary hippocampal neurons were isolated, cell viability was detected by MTT assay and intracellular Ca2+ concentration was detected by calcium imaging assay. The content of Nitriteoxide (NO), Malondialdehyde (MDA) and Superoxide dismutase (SOD) activity in serum of rats were observed by Enzyme Linked Immunosorbent Assay (ELISA). Immunohistochemistry, Western blot, and Confocal laser scanning were used to detect the expression levels of N-methyl-d-asprtate receptor-2B (NR2B) and TRPM2. Results The results showed that PAE can improve the number and activity of neurons, increase the length and number of dendrites in hippocampus, decrease the Vv value and PE value of neuronal nucleus and mitochondrial structure significantly, increase the s value and L value in nucleus structure, decrease the s value and L value in mitochondrial structure, and improve the learning and memory ability of rats significantly. And PAE can strengthen the ability of antioxidant stress confirmed by increasing the activity of SOD and reducing the production of MDA. The results of western blot, immunohistochemistry and immunofluorescence showed that PAE could reduce the level of TRPM2 and increase the expression of NR2B. Conclusions Taken together, our findings provide evidence that the neuroprotective effects of PAE in VD rats maybe through TRPM2 inhibition and subsequent activation of NMDAR signaling pathway.